Micro‐ and macro‐morphology of the olfactory organ of Syngnathus typhle (Syngnathidae, Actinopterygii). (23rd March 2020) - Dymek, Jakub; Rosenqwist, Gunilla; Kuciel, Michał; Lauriano, Eugenia Rita; Capillo, Gioele; Zaccone, Giacomo; Żuwała, Krystyna
Abstract: Herein, we describe the micro‐ and macro‐morphology of the olfactory organ in broad‐nosed pipefish ( Syngnathus typhle ) with a comparison of this organ between males and females during breeding season. With 8 adult males, 8 females, and 7 pregnant males collected during the breeding season from the Baltic sea as our samples, our research was conducted using light and electron (TEM, SEM) microscopes and immunohistochemistry methods to distinguish the olfactory sensory neurons. The interior of the olfactory chamber lacked an olfactory rosette. Instead, olfactory receptor epithelium covered the inner walls of the olfactory chamber and, to varying degrees, the inside of the anterior and posterior nostrils. All types of olfactory sensory neurons (ciliated, microvillus, and crypt) were present within the olfactory sensory epithelium, although the crypt sensory neurons were limited to the pregnant and non‐pregnant males). The olfactory sensory neurons were present in the areas where the density of the non‐sensory epithelium cells was reduced. No significant differences in morphology of the olfactory organ between sexes were found. Nevertheless, only in males crypt sensory neurons were presented in olfactory epithelium, which indicates that sense of smell could play a little role during mating.